A positive feedback loop between SMAD3 and PINK1 in regulation of mitophagy - Mingzhu Tang; Dade Rong; Xiangzheng Gao; Guang Lu; Haimei Tang; Peng Wang; Ning-Yi Shao; Dajing Xia; Xin-Hua Feng; Wei-Feng He; Weilin Chen; Jia-Hong Lu; et al. (Cell Discovery)
Abstract PTEN-induced kinase-1 (PINK1) is a crucial player in selective clearance of damaged mitochondria via the autophagy-lysosome pathway, a process termed mitophagy. Previous studies on PINK1 mainly focused on its post-translational modifications, while the transcriptional regulation of PINK1 is much less understood. Herein, we reported a novel mechanism in control of PINK1 transcription by SMAD Family Member 3 (SMAD3), an essential component of the transforming growth factor beta (TGFβ)-SMAD signaling pathway. First, we observed that mitochondrial depolarization promotes PINK1 transcription, and SMAD3 is likely to be the nuclear transcription factor mediating PINK1 transcription. Intriguingly, SMAD3 positively transactivates PINK1 transcription independent of the canonical TGFβ signaling components, such as TGFβ-R1, SMAD2 or SMAD4. Second, we found that mitochondrial depolarization activates SMAD3 via PINK1-mediated phosphorylation of SMAD3 at serine 423/425. Therefore, PINK1 and SMAD3 constitute a positive feedforward loop in control of mitophagy. Finally, activation of PINK1 transcription by SMAD3 provides an important pro-survival signal, as depletion of SMAD3 sensitizes cells to cell death caused by mitochondrial stress. In summary, our findings identify a non-canonical function of SMAD3 as a nuclear transcriptional factor in regulation of PINK1 transcription and mitophagy and a positive feedback loop via PINK1-mediated SMAD3 phosphorylation and activation. Understanding this novel regulatory mechanism provides a deeper insight into the pathological function of PINK1 in the pathogenesis of neurodegenerative diseases such as Parkinson's disease.